Development of Android-Based E-Module Media through Problem Based Learning on Enviromental Change Material to Improve Critical Thinking - Nazlafatin Hamida; Nur Rahayu Utami (Journal of Biology Education, 2024)
This research was motivated by the use of androids in schools after the pandemic, which caused students' learning concentration to be disrupted and the learning model to be less attractive. Students prefer learning models that are more interesting than learning models using the lecture method. One of the interesting learning models is e-module media. E-Module offers easy interactive navigation for its users, which can be applied via Android. The object of this research is the students of Class X, SMA N 12, Semarang. This research is a type of Research and Development (R&D) 4D model, but it is only carried out in three stages: define, design, and develop. The results of this study indicate that the developed e-module media is very suitable for use as a learning medium. This can be seen from the average validation score percentage of media experts of 94.5%, which is a very decent category. The percentage of the average validation score of material experts is 91,5%, which is a very decent category. The results of the readability test questionnaire were 88,1% in the very decent category. There is an increase in students' critical thinking through the N-gain test of 9% in the low category, 31% in the medium category, and 60% in the high category, where as many as > 80% of students get the medium to high category of increased critical thinking or N-gain > 0,3. Based on the results of this study, it can be concluded that the android-based e-module through problem-based learning is very feasible to use and can improve students' critical thinking on environmental change material.